SIKAP REMAJA TERHADAP IKLAN KONDOM - Yunan Surono (Universitas Batanghari Jambi, 2015)
Advertising is growing rapidly as mass media done. Television is one of the most favorable medium of advertising because of its ability to show the visualization, both the audio. DKT Indonesia, as an advertiser, uses the Television Commercial with an animation concept to communicate their product and also the message, which is dedicated for adolescents. Based on the reality, the subject of this research is Jambi City adolescent, which the average age is 10 until 24 years old. Researcher wants to know the attitude of adolescents to Condom Television Commercial. The result said that the attitude of adolescents was neutral, which is the cognitive and affective level are neutral, but the behavioral is negativeKey Word: Condom Television Commercial